'Motor Merdeka Atuk' fosters patriotism and love for the nation - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 30 August 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has produced a short drama titled 'Motor Merdeka Atuk' in conjunction with the 67th Independence Day, which will be celebrated on 31 August.